A Meta-Analysis of Rupture Risk for Intracranial Aneurysms 10 mm or Less in Size Selected for Conservative Management Without Repair - Chandra, Ronil V.; Maingard, Julian; Slater, Lee-Anne; Cheung, Nicholas K.; Lai, Leon T.; Gall, Seana L.; Thrift, Amanda G.; Phan, Thanh G. (Frontiers in Neurology, 2022)
BACKGROUND: Small unruptured intracranial aneurysms (UIAs) are considered to have low risk of rupture. The proportion of UIAs measuring 10 mm or less in size that rupture when selected for conservative management without repair is not well known. The aim of this study is to determine the proportion of UIAs that rupture by size threshold from ≤10 mm to ≤3mm when selected for management without repair, and to determine the level of precision and sources of heterogeneity in the rupture risk estimate. METHODS: The review was prospectively registered with PROSPERO (CRD42019121522). The MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials were searched (inception-August 2020). Studies with longitudinal follow-up of patients with UIAs (≤10 mm to ≤3mm) without endovascular or neurosurgical repair were eligible. We included studies which provided details of aneurysm size, and in which UIA rupture was reported as an outcome. The primary outcome of the pooled proportion of UIA rupture during follow-up was synthesised with random-effects meta-analysis; heterogeneity was explored using meta-regression. RESULTS: A total of 31 studies that included 13800 UIAs ≤10 mm in size were eligible for data synthesis. The pooled proportion of ≤10 mm UIAs that ruptured when managed without repair was 1.1% (95%CI 0.8–1.5; I2=52.9%) over 3.7 years. Findings were consistent in sensitivity analyses at all size stratified thresholds including ≤5mm and ≤3mm; rupture occurred in 1.0% [95% CI 0.8–1.3; I2=0%] of 7280 ≤5mm UIAs and 0.8% [95% CI 0.4–1.5; I2=0%] of 1228 ≤3mm UIAs managed without repair. In higher quality studies with lower risk of bias, rupture occurred in 1.8% (95% CI 1.5–2.0; I2=0%) over 3.9 years. In meta-regression, aneurysm size, shape, anatomical location, and exposure to prior subarachnoid haemorrhage was not identified as sources of heterogeneity. CONCLUSION: For every 1000 UIAs that are 10 mm or less in size, and selected for conservative management without repair, between 8 to 15 are estimated to rupture over 3.7 years. When stratified by size, these pooled rupture risk estimates are consistent and clinically applicable for ≤5mm UIAs selected for management without repair.